ARCHITECTURE OF PALACE KUYI HAULI (Web of Teachers: Inderscience Research, 2024)
In addition to the above, the formation of the architecture of the palaces reflected the most important, stagnation of architectural traditions, local natural and climatic conditions, religious, social and moral values, and customs. The architecture of Bukhara palaces reflected the heavenly courtyards characteristic of the architecture of the countries of the Islamic East with a hot and dry climate, the phenomenon of internal and external courtyards, as well as the forms of porches, awnings, awnings, pools, fountains, gardens, garden-palaces, walking areas, flower beds.